The Influence of Leadership Style, Employee Training, Intrinsic Reward, and Extrinsic Reward on Employee Motivation - Oda I.B. Hariyanto; Haverina Haverina (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This research aimed to know if leadership style, employee training, intrinsic reward, and extrinsic reward had a significant relationship toward employee motivation. Data collected from 221 respondents who were employees of Tour & Travel Agents in Batam. The sampling method used was purposive sampling which took sample with some consideration. The result shows that all of them have positive significance to employee motivation. Besides, employee training has the greatest amount of significance on employee motivation.